Gender differences on bias of IPO earnings forecasts - Ahmad Zaluki, Nurwati Ashikkin (Medwell Journals, 2016)
This study investigates whether the gender differences of audit committees influences the bias of earnings forecasts. Using earnings forecasts data disclosed in the IPO prospectuses, this study made a comparison with the actual earnings reported in the first publish annual reports to identify such bias. The bias in earnings forecast is divided into two components: pessimistic and optimistic. The uni-variate analysis is applied using IPO companies that went public during the period 1999-2008 where the requirement on earnings forecast disclosure in Malaysia is mandatory. This study finds that companies having female directors on the audit committee have greater negative forecast errors (optimists forecasts bias) than companies having only male audit committee.